Copper-doped bismuth-based material and preparation method and application thereof

By in-situ electrochemical reduction of different proportions of copper-doped bismuth-based organic layers, nanosheet-shaped copper-doped bismuth-based electrocatalysts were prepared, which solved the problem of low CO2 reduction efficiency in acidic electrolytes and achieved efficient CO2 reduction performance. Especially under industrial current.

CN119332300AActive Publication Date: 2025-01-21EAST CHINA UNIV OF SCI & TECH

Patent Information

Application Number
CN202411780518.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-21
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

Under industrial currents, CO2 reduction in acidic electrolytes is limited by competitive hydrogen evolution reactions, resulting in a decrease in CO2 reduction efficiency of bismuth-based catalysts.

Method used

By electrochemical restoration of different proportions of copper -doped ingu -based organic layers, nano -sheet -shaped copper -doped catalyst catalysts are prepared, which increases the activity site and surface area of ​​the catalyst.

Benefits of technology

Under the industrial -grade current density of 400mA/CM2, the methacology Faraid of the copper doped catalyst catalyst reached 87.1%, and when the CO2 gas flow rate at 300mA/CM2 was 3SCCM, the one -way conversion efficiency was as high as 62.1%, which was significantly improved, significantly improved, significantly improved, significantly improved CO2 restore performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332300A_ABST
    Figure CN119332300A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-doped bismuth-based material as well as a preparation method and application thereof, and the method comprises the following steps: preparing a nano flaky copper-doped bismuth-based material from a copper-doped bismuth-based organic layer by an electrochemical reduction method. And the copper-doped bismuth-based organic layer is prepared by a hydrothermal method. The copper-doped bismuth-based material is used as an electrocatalyst in reduction of CO2 in an acidic system. According to the copper-doped bismuth-based material, the problem of how to increase electron-rich bismuth active sites is solved, and good efficiency of preparing formic acid through reduction of CO2 under electro-catalysis in an acidic electrolyte is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a copper-doped bismuth-based material and a preparation method and application thereof. Background Art

[0002] Renewable electricity-driven electrocatalytic CO2 reduction is an effective decarbonization strategy for converting CO2 into high-value chemicals and fuels. CO2 reduction in alkaline or neutral electrolytes provides a strong alkaline microenvironment at the cathode interface, effectively inhibiting the competitive hydrogen evolution reaction. However, CO2 molecules easily react with hydroxides to form carbonates, which may cross the anion exchange membrane to reach the anode, thereby consuming CO2 feedstock and reducing carbon utilization efficiency. In addition, carbonates can block the gas channels for CO2 transport, posing a huge threat to the stability of the CO2 reduction system.

[0003] CO2 reduction in acidic electrolytes can solve the above problems to a certain extent. The high proton concentration in the acidic electrolyte and the use of cation exchange membranes can prevent the formation of carbonates and the crossover of liquid products to the anode. Formic acid has been proven to be the most technically and economically promising liquid product in CO2 reduction. The reduction of CO2 in acidic electrolytes directly produces formic acid rather than formate, which is easy to extract and purify. Bismuth has become a typical metal for reducing CO2 due to its environmental friendliness, abundant reserves, and high selectivity for reducing CO2 to formic acid. For the acidic CO2 reduction over bismuth-based catalysts, Li et al. prepared electron-rich bismuth nanosheets that reacted at 100 mA·cm -2 Chen et al. obtained indium-doped Bi / BiO by in-situ electroreduction. x Nanosheet, at 200mAcm -2 The maximum formic acid Faradaic efficiency is 96% under the condition of current density exceeding 300mAcm -2 When the reaction is carried out under acidic conditions, CO2 reduction is significantly limited due to the kinetics of the competitive hydrogen evolution reaction in acidic electrolytes. Therefore, it is crucial to promote the reduction of CO2 to formic acid by bismuth-based catalysts in acidic systems at industrial currents. Summary of the invention

[0004] The purpose of the present invention is to provide a copper-doped bismuth-based material and a preparation method and application thereof. The present invention obtains a copper-doped bismuth-based electrocatalyst by in-situ electrochemical reduction of copper-doped bismuth-based organic layers in different proportions.

[0005] In one aspect of the present invention, the present invention provides a method for preparing a copper-doped bismuth-based material. According to an embodiment of the present invention, the method comprises the following steps: electrochemically reducing a copper-doped bismuth-based organic layer to prepare a nano-sheet copper-doped bismuth-based material.

[0006] In addition, the method for preparing a copper-doped bismuth-based material according to the above embodiment of the present invention may also have the following additional technical features:

[0007] In some embodiments of the present invention, the method for preparing the copper-doped bismuth-based organic layer is as follows: a bismuth source precursor, a copper source precursor and a small molecule organic matter are mixed, and then prepared by a hydrothermal method.

[0008] In some embodiments of the present invention, the bismuth source precursor is one or both of bismuth nitrate and bismuth chloride, the copper source precursor is one or both of copper nitrate and copper chloride, the small molecule organic matter is imidazoles and piperazine, and the molar ratio of the bismuth source precursor to the copper source precursor is (5:1) to (100:1).

[0009] In some embodiments of the present invention, the temperature of the hydrothermal method is 120-180° C. and the time is 12-72 hours.

[0010] In some embodiments of the present invention, the copper-doped bismuth-based organic layer is composed of a block structure.

[0011] In some embodiments of the present invention, the electrochemical reduction method comprises the following steps: dispersing the copper-doped bismuth-based organic layer and the perfluorosulfonic acid-polytetrafluoroethylene copolymer solution in ethanol, ultrasonically obtaining an ethanol dispersion, uniformly spraying the ethanol dispersion on a hydrophobic carbon paper to form a working electrode, and then using Ag / AgCl saturated with KCl as a reference electrode and a platinum electrode as a counter electrode to perform in situ electrochemical reduction.

[0012] In some embodiments of the present invention, the amount of the copper-doped bismuth-based organic layer and the perfluorosulfonic acid-polytetrafluoroethylene copolymer solution is 0.1-2 mg / μL, the amount of the copper-doped bismuth-based organic layer relative to ethanol is 1-50 mg / mL, the frequency of the ultrasound is 10-50 KHz, and the ultrasound time is 20-60 minutes.

[0013] In some embodiments of the present invention, the electrochemical reduction is to activate the working electrode in the potential range of -1.0 to -1.8 V relative to the Ag / AgCl electrode by cyclic voltammetry, with a scan rate of 10-100 mV / s; and cycle 50-200 times in an acidic electrolyte.

[0014] In another aspect of the present invention, the present invention provides a copper-doped bismuth-based material prepared according to the method for preparing the copper-doped bismuth-based material. According to an embodiment of the present invention, the copper-doped bismuth-based material is in a nanosheet shape with a length and width of 1 to 10 μm and a thickness of 5 to 30 nm.

[0015] In another aspect of the present invention, the present invention provides an application of the copper-doped bismuth-based material. According to an embodiment of the present invention, the copper-doped bismuth-based material is used as an electrocatalyst in the reduction of CO2 in an acidic system.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] (1) The present invention adopts a hydrothermal method to synthesize a copper-doped bismuth-based organic layer precatalyst. The synthesis method is simple and the reaction conditions are mild. The obtained material is easy to use and is conducive to promotion and application in industrial production.

[0018] (2) The copper-doped bismuth-based electrocatalyst of the present invention has excellent CO2 reduction performance in acidic electrolytes at 400 mA / cm 2 At an industrial current density of 300 mA / cm 2 When the CO2 gas flow rate is 3 sccm, the single-pass conversion efficiency is as high as 62.1%.

[0019] (3) The present invention first prepares a copper-doped bismuth-based organic layer pre-catalyst, wherein there is electron transfer between bismuth and copper, and bismuth serves as an electron acceptor, thereby increasing electron-rich bismuth active sites. A nanosheet copper-doped bismuth-based catalyst is obtained by in-situ electroreduction of the organic layer, further increasing the exposure of the active sites. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Bi prepared in Example 1 of the present invention 20 XRD pattern of Cu-NS catalyst;

[0021] Figure 2 Bi prepared in Example 1 of the present invention 20 SEM images of Cu-NS catalyst at low (left) and high (right) magnifications;

[0022] Figure 3 Bi prepared in Example 1 of the present invention 20 TEM image of Cu-NS catalyst at low magnification;

[0023] Figure 4 Bi prepared in Example 1 of the present invention 20 TEM image of Cu-NS catalyst at high magnification;

[0024] Figure 5 Bi prepared in Example 1 of the present invention 20 HAADF-STEM image, Bi, Cu and O elemental mapping images of Cu-NS catalyst;

[0025] Figure 6The Bi-NS prepared in the comparative example of the present invention and the Bi prepared in Example 1-2 are x Bi 4fXPS spectrum of Cu organic layer;

[0026] Figure 7 Bi prepared in Examples 1-3 of the present invention x Cu 2p XPS spectrum of Cu organic layer;

[0027] Figure 8 The Bi-NS prepared in the comparative example of the present invention and the Bi prepared in Example 1-2 are x LSV curve of Cu-NS catalyst;

[0028] Fig. 9 The Bi-NS prepared in the comparative example of the present invention and the Bi prepared in Example 1 are x Faradaic efficiency of formic acid for Cu-NS catalyst at different applied current densities;

[0029] Fig.10 The Bi-NS prepared in the comparative example of the present invention and the Bi prepared in Example 1 are 20 Energy efficiency and voltage of formic acid cathode of Cu-NS catalyst at different applied current densities;

[0030] Fig.11 Bi prepared in Example 1 of the present invention 20 Stability test diagram of Cu-NS catalyst;

[0031] Fig.12 Bi prepared in Example 1 of the present invention 20 Cu-NS catalyst at 300mA / cm 2 Single-pass conversion efficiency diagram at different CO2 flow rates;

[0032] Fig.13 The Bi-NS prepared in the comparative example of the present invention and the Bi prepared in Example 1-2 are x Electrochemical impedance spectroscopy of Cu-NS electrocatalyst;

[0033] Fig.14 The Bi-NS prepared in the comparative example of the present invention and the Bi prepared in Example 1-2 are x Double-layer capacitance diagram of Cu-NS electrocatalyst. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] Copper-doped bismuth-based material Bi with a bismuth-copper molar ratio of 20:1 20 The preparation method of Cu-NS comprises the following steps:

[0037] (1) 2 mmol of bismuth nitrate pentahydrate, 0.1 mmol of copper nitrate trihydrate, 4 mmol of 4,5-imidazole dicarboxylic acid and 2 mmol of piperazine were added to 20 mL of deionized water and stirred vigorously for 60 minutes.

[0038] (2) The mixed solution was subjected to hydrothermal reaction at 170°C for 24 hours. The precipitate was collected and washed with deionized water and anhydrous ethanol for several times by centrifugation, and then dried in a vacuum oven at 60°C for 24 hours to obtain Bi 20 Cu organic layer.

[0039] (3) Prepared Bi 20 10 mg of Cu organic layer and 40 μL of Nafion solution (5 wt%) were dispersed in 960 μL of ethanol and sprayed evenly on hydrophobic carbon paper as the working electrode after ultrasonic treatment for 60 minutes. The catalyst loading was controlled at 1.0 mg / cm 2 The above electrode was used as the working electrode (1×1cm 2 ), Ag / AgCl electrode (saturated with KCl) as reference electrode, platinum mesh electrode as counter electrode (0.7×1.5cm 2 ), the working electrode was activated in the potential range of -1.0 to -1.8 V relative to the Ag / AgCl electrode by cyclic voltammetry, the scan rate was 50 mV / s, and the cycle was repeated 100 times in an acidic electrolyte (1 M Cs2SO4 mixed with dilute H2SO4, pH adjusted to 2) to obtain a nanosheet copper-doped bismuth-based catalyst (denoted as Bi 20 Cu-NS).

[0040] The prepared copper-doped bismuth-based material has a nano-sheet morphology with a length and width of 1 μm-10 μm and a thickness of 5 nm-30 nm.

[0041] The prepared Bi 20 Cu-NS electrocatalyst was subjected to XRD test, such as Figure 1As shown in Figure 2, there is a sharp peak corresponding to metallic Bi at 27°, indicating that the Bi2O3 species tends to be reduced after electroreduction. The presence of some small peaks attributed to Bi2O3 may be due to the presence of adsorbed oxygen on the surface of the material.

[0042] like Figure 2 As shown, SEM images at different magnifications reveal that Bi 20 The nanosheet structure of Cu-NS has micrometer-scale wrinkles, which increases its surface area. Due to the curved geometry, Bi 20 The significant tensile strain in Cu-NS can adjust the electronic structure of Bi atoms, thereby improving the adsorption capacity of key reaction intermediates. Figure 3 As shown, TEM images further show that Bi 20 Cu-NS has an ultrathin stacked nanosheet structure, so it has abundant active sites. Figure 4 As shown, high-resolution TEM images show lattice spacings of 0.35 and 0.34 nm, corresponding to the (012) crystal plane of Bi and the (111) crystal plane of Bi2O3, respectively. Figure 5 As shown, the elemental composition and distribution were investigated using HAADF-STEM-EDS elemental mapping. Bi and Cu elements were uniformly distributed with no signs of phase separation. The presence of O element was attributed to the fact that Bi was easily oxidized when exposed to air.

[0043] Example 2

[0044] Copper-doped bismuth-based material Bi with a bismuth-copper molar ratio of 50:1 50 The preparation method of Cu-NS comprises the following steps:

[0045] (1) 2 mmol of bismuth nitrate pentahydrate, 0.04 mmol of copper nitrate trihydrate, 4 mmol of 4,5-imidazole dicarboxylic acid and 2 mmol of piperazine were added to 20 mL of deionized water and stirred vigorously for 60 minutes.

[0046] (2) The mixed solution was subjected to hydrothermal reaction at 170°C for 24 hours. The precipitate was collected and washed with deionized water and anhydrous ethanol for several times by centrifugation, and then dried in a vacuum oven at 60°C for 24 hours to obtain Bi 50 Cu organic layer.

[0047] (3) Prepared Bi 50 10 mg of Cu organic layer and 40 μL of Nafion solution (5 wt%) were dispersed in 960 μL of ethanol and sprayed evenly on hydrophobic carbon paper as the working electrode after ultrasonic treatment for 60 minutes. The catalyst loading was controlled at 1.0 mg / cm 2 The above electrode was used as the working electrode (1×1cm 2), Ag / AgCl electrode (saturated KCl) as reference electrode, platinum mesh electrode as counter electrode (0.7×1.5cm 2 ), the working electrode was activated in the potential range of -1.0 to -1.8 V relative to the Ag / AgCl electrode by cyclic voltammetry, the scan rate was 50 mV / s, and the cycle was repeated 100 times in an acidic electrolyte (1 M Cs2SO4 mixed with dilute H2SO4, pH adjusted to 2) to obtain a nanosheet copper-doped bismuth-based catalyst (denoted as Bi 50 Cu-NS).

[0048] Bi and Bi prepared in Example 1-2 x XPS characterization of Cu organic layer:

[0049] Bi x XPS tests were performed on the Cu and Bi organic layers to study the chemical state of the elements in the pre-catalyst, and the binding energy of the C1s peak was set to 284.8 eV as a reference. Figure 6 As shown in the Bi 4f spectrum, the peaks at 164.4 and 159.0 eV are attributed to the Bi 4f 7 / 2 and Bi 4f 5 / 2 , indicating the Bi2O3 phase on the surface of the material.

[0050] Example 3

[0051] Copper-doped bismuth-based material Bi with a bismuth-copper molar ratio of 99:1 99 The preparation method of Cu-NS comprises the following steps:

[0052] (1) 2 mmol of bismuth nitrate pentahydrate, 0.02 mmol of copper nitrate trihydrate, 4 mmol of 4,5-imidazole dicarboxylic acid and 2 mmol of piperazine were added to 20 mL of deionized water and stirred vigorously for 60 minutes.

[0053] (2) The mixed solution was subjected to hydrothermal reaction at 170°C for 24 hours. The precipitate was collected and washed with deionized water and anhydrous ethanol for several times by centrifugation, and then dried in a vacuum oven at 60°C for 24 hours to obtain Bi 99 Cu organic layer.

[0054] (3) Prepared Bi 99 10 mg of Cu organic layer and 40 μL of Nafion solution (5 wt%) were dispersed in 960 μL of ethanol and sprayed evenly on hydrophobic carbon paper as the working electrode after ultrasonic treatment for 60 minutes. The catalyst loading was controlled at 1.0 mg / cm 2 The above electrode was used as the working electrode (1×1cm 2 ), Ag / AgCl electrode (saturated KCl) as reference electrode, platinum mesh electrode as counter electrode (0.7×1.5cm2 ), the working electrode was activated in the potential range of -1.0 to -1.8 V relative to the Ag / AgCl electrode by cyclic voltammetry, the scan rate was 50 mV / s, and the cycle was repeated 100 times in an acidic electrolyte (1 M Cs2SO4 mixed with dilute H2SO4, pH adjusted to 2) to obtain a nanosheet copper-doped bismuth-based catalyst (denoted as Bi 99 Cu-NS).

[0055] like Figure 7 As shown, Bi 50 Cu and Bi 20 The Cu 2p spectrum of the Cu organic layer shows that it corresponds to Cu 2p 1 / 2 and Cu 2p 3 / 2 Peak. 99 Compared with the Cu 2p spectrum of Cu organic layer, due to the trace amount of Cu doping, Bi 99 The Cu organic layer only shows the Cu 2p 3 / 2 The characteristic peaks of Figure 6 As the Cu content increases, the Bi 4f spectrum shifts negatively and the Cu 2p spectrum shifts positively. Compared with the Bi organic layer without copper doping, the Bi 50 Cu and Bi 20 The Bi 4f of Cu organic layer shifts to the low binding energy region by 0.25 and 0.45 eV. 99 Compared with Cu organic layer, Bi 50 Cu and Bi 20 The Cu 2p of the Cu organic layer moved to the high binding energy region by 0.09 and 0.19 eV. The above results indicate that there is electron transfer between Bi and Cu, and Bi acts as an electron acceptor. The electron interaction is expected to be regulated by Bi x The interfacial electronic structure of the Cu organic layer-derived catalyst was optimized to optimize the Bi active sites for formic acid production.

[0056] Comparative Example

[0057] The method for preparing the copper-free bismuth-based material Bi-NS comprises the following steps:

[0058] (1) 2 mmol of bismuth nitrate pentahydrate, 4 mmol of 4,5-imidazole dicarboxylic acid and 2 mmol of piperazine were added to 20 mL of deionized water and stirred vigorously for 60 minutes.

[0059] (2) The mixed solution was subjected to hydrothermal reaction at 170° C. for 24 hours. The precipitate was collected and washed with deionized water and anhydrous ethanol for several times by centrifugation, and dried in a vacuum oven at 60° C. for 24 hours to obtain a Bi organic layer.

[0060] (3) 10 mg of the prepared Bi organic layer powder and 40 μL of Nafion solution (5 wt%) were dispersed in 960 μL of ethanol and, after ultrasonic treatment for 60 minutes, uniformly sprayed on a hydrophobic carbon paper as a working electrode. The catalyst loading was controlled at 1.0 mg / cm 2 The above electrode was used as the working electrode (1×1cm 2 ), Ag / AgCl electrode (saturated with KCl) as reference electrode, platinum mesh electrode as counter electrode (0.7×1.5cm 2 ), the working electrode was activated by cyclic voltammetry in the potential range of -1.0 to -1.8 V relative to the Ag / AgCl electrode, with a scan rate of 50 mV / s, and cycled 100 times in an acidic electrolyte (1 M Cs2SO4 mixed with dilute H2SO4, pH adjusted to 2) to obtain a nanosheet copper-doped bismuth-based catalyst (denoted as Bi-NS).

[0061] Application Examples

[0062] Bi-NS prepared in the comparative example and Bi prepared in Examples 1-3 x Cu-NS electrocatalyst for CO2 reduction in acidic system:

[0063] CO2 reduction was performed in a flow electrolysis cell connected to an electrochemical workstation (CHI 760e). x Cu-NS electrocatalyst (1.0 mg / cm 2 ) gas diffusion electrode (1×1cm 2 ), platinum mesh (0.7×1.5cm 2 ) and KCl-saturated Ag / AgCl electrodes were used as cathode, anode and reference electrodes, respectively. The catholyte and anolyte compartments were composed of cation exchange membranes (CEM, 117). During the measurement, CO2 gas (20 sccm) was supplied to the cathode gas diffusion layer. The anolyte and catholyte were 0.05 M H2SO4 and 1 M Cs2SO4 (the pH was adjusted to 2 with H2SO4). The electrolyte flow rate was controlled at 15 mL min -1 .

[0064] Linear sweep voltammetry (LSV) curve is as follows Figure 8 As shown, at 50mV s -1 The LSV curve was measured at a scan rate of 20 Cu-NS showed a higher current density than the comparative example at -2.55 V RHE Up to 400mAcm -2 .

[0065] The Faradaic efficiency of formic acid is Fig. 9As shown, at 50 to 400 mA / cm 2 In a wide current density range, Bi 20 The high formic acid Faradaic efficiency obtained for Cu-NS demonstrates its excellent performance. 2 At high current density, Bi 20 The formic acid Faradaic efficiency of Cu-NS is 87.1%. 2 The maximum Faraday efficiency reaches 91.3% when the Bi-NS catalyst is 150 mA / cm 2 The maximum formic acid Faradaic efficiency reaches 92.5% when 2 At the beginning, the CO2 reduction performance of Bi-NS electrocatalyst in acidic system was significantly reduced, and the Faraday efficiency of formic acid was 400 mA / cm 2 When the temperature decreases to 32.6%. 20 Cu-NS achieves high formic acid Faradaic efficiency (~90%) at all applied current densities, while the comparative examples have low formic acid efficiency between 200 and 400 mA cm -2 High performance cannot be maintained over the high current density range.

[0066] Cathode energy efficiency and potential Fig.10 As shown, Bi-NS and Bi 20 The cathode energy efficiency of Cu-NS electrocatalyst is between 100 and 300 mA / cm 2 In the current density range, Bi 20 The cathode energy efficiency of Cu-NS is higher than that of Bi-NS. 2 When the cathode energy efficiency is 54.1%, 20 The potential of Cu-NS is lower than that of Bi-NS at all applied current densities.

[0067] In addition to activity and selectivity, stability is also a key parameter for evaluating the application prospects of electrocatalysts. Fig.11 As shown, at pH 2, 2 M Cs + In electrolyte, at 200 mA / cm 2 The effect of constant current density on Bi 20 Cu-NS was subjected to long-term CO2 reduction test. The formic acid Faradaic efficiency remained at about 90% for 40 h without obvious decay, indicating its excellent stability.

[0068] The single-pass conversion efficiency is Fig.12 As shown, at 300mA / cm 2 At a current density of 2.5, when the CO2 gas flow rate is 3 sccm, Bi 20The single-pass conversion efficiency of Cu-NS is as high as 62.1%, revealing the superiority of acidic electrolytes in CO2 utilization.

[0069] like Fig.13 As shown, electrochemical impedance spectroscopy was performed by applying a voltage of -0.9 V to study the charge transfer. 20 Cu-NS showed a smaller charge transfer resistance than the control, reflecting its faster charge transfer kinetics. Fig.14 The electrochemical double layer capacitance (C dl ), Bi 20 Twice the C of Cu-NS dl 3.69mF / cm 2 , higher than Bi-NS (2.21mF / cm 2 ) and Bi 50 Cu-NS (1.38 mF / cm). Bi 20 The larger electrochemical active area of ​​Cu-NS provides more catalytic active sites for CO2 reduction in acidic systems, thus achieving excellent activity. When the molar ratio of bismuth to copper elements is 20:1, the bimetallic synergistic effect is optimal. The resulting electron-rich bismuth-based nanosheets have enhanced intrinsic activity and charge transfer behavior, showing the best performance in acidic CO2 reduction to produce formic acid.

[0070] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a copper-doped bismuth-based material, characterized in that: The following steps are involved: The copper-doped bismuth-based organic layer is subjected to an electrochemical reduction method to prepare a nano-sheet copper-doped bismuth-based material.

2. The method for preparing a copper-doped bismuth-based material according to claim 1, characterized in that: The preparation method of the copper-doped bismuth-based organic layer is as follows: a bismuth source precursor, a copper source precursor and a small molecule organic matter are mixed, and then prepared by a hydrothermal method.

3. The method for preparing a copper-doped bismuth-based material according to claim 2, characterized in that: The bismuth source precursor is one or both of bismuth nitrate and bismuth chloride, the copper source precursor is one or both of copper nitrate and copper chloride, the small molecule organic matter is imidazoles and piperazine, and the molar ratio of the bismuth source precursor to the copper source precursor is (5:1) to (100:1).

4. The method for preparing a copper-doped bismuth-based material according to claim 2, characterized in that: The temperature of the hydrothermal method is 120-180° C. and the time is 12-72 hours.

5. The method for preparing a copper-doped bismuth-based material according to claim 1, characterized in that: The copper-doped bismuth-based organic layer consists of a block structure.

6. The method for preparing a copper-doped bismuth-based material according to claim 1, characterized in that: The electrochemical reduction method comprises the following steps: dispersing a copper-doped bismuth-based organic layer and a perfluorosulfonic acid-polytetrafluoroethylene copolymer solution in ethanol, ultrasonically obtaining an ethanol dispersion, uniformly spraying the ethanol dispersion on a hydrophobic carbon paper to prepare a working electrode, and then performing in-situ electrochemical reduction using Ag / AgCl saturated with KCl as a reference electrode and a platinum electrode as a counter electrode.

7. The method for preparing a copper-doped bismuth-based material according to claim 6, characterized in that: The dosage of the copper-doped bismuth-based organic layer and the perfluorosulfonic acid-polytetrafluoroethylene copolymer solution is 0.1-2 mg / μL, the dosage of the copper-doped bismuth-based organic layer relative to ethanol is 1-50 mg / mL, the frequency of the ultrasound is 10-50 KHz, and the ultrasound time is 20-60 minutes.

8. The method for preparing a copper-doped bismuth-based material according to claim 6, characterized in that: The electrochemical reduction is to activate the working electrode in the potential range of -1.0 to -1.8 V relative to the Ag / AgCl electrode by cyclic voltammetry, with a scanning rate of 10-100 mV / s; and circulate 50-200 times in an acidic electrolyte.

9. A copper-doped bismuth-based material prepared according to the method for preparing a copper-doped bismuth-based material according to any one of claims 1 to 8, characterized in that: The copper-doped bismuth-based material is in the shape of a nano-sheet, with a length and width of 1 to 10 μm and a thickness of 5 to 30 nm.

10. An application of the copper-doped bismuth-based material according to claim 9, characterized in that: The copper-doped bismuth-based material is used as an electrocatalyst in the reduction of CO2 in an acidic system.

Citation Information

Patent Citations

  • Bismuth-doped zinc-based metal organic framework material as well as preparation method and application thereof

    CN115747845A

  • Bismuth-copper bimetallic composite catalyst for electroreduction of carbon dioxide as well as preparation method and application of bismuth-copper bimetallic composite catalyst

    CN117721495A

  • Organic functionalized bismuth catalyst electrode as well as preparation method and application thereof

    CN118326463A

  • Photocathode with CO2 adsorption capacity and photoelectrocatalysis CO2 reduction as well as preparation method and application of photocathode

    CN118957654A

Cited By

  • Cationic polymer coated copper-based catalyst as well as preparation method and application thereof

    CN120041883A